Pengaruh Product, Price, Place Dan Promotion Terhadap Keputusan Nasabah Simpanan Fleximax Di PT. Bank Panin Dubai Syariah KCU Bandung - Gina Sakinah; Ade Ponirah; Intan Nurjanah (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
Companies are required to be able to compete in the world of marketing. Because the heart of the company lies in the world of marketing. In order for the company's operations to run smoothly, the marketing process must run well. There are several factors that must be considered by the management team in determining a marketing strategy known as the marketing mix. In this article, we will analyze the effect of Product, Price, Place and Promotion on Customer Decisions for Fleximax Savings Bank Panin Dubai Syariah KCU Bandung. Product is everything that is ready to be marketed by producers to get attention, requested until purchased to fulfill needs. Price is the value of an item or service that is measured in money to get the goods or benefits. Place is a permanent location or existence of a company. Promotion is sales communication that is persuasive in influencing consumers to be interested in the products offered. The results of the research show that all independent variables have an effect on the dependent variable. First, the results of the first t-test, obtained a t-test of 2.232 with a significance level of 0.029, meaning that the product is able to have a significant influence on the decision of the Fleximax Savings Customer partially; Second, the results of the t-test obtained a t-test of 2.128 with a significance level of 0.037, meaning that Price is able to give a significant influence on the decision of the Fleximax Savings Customer partially; Third, the results of the t-test obtained t-test 3.346 with a significance level of 0.001, meaning that Place is able to have a significant influence on the decision of the Fleximax Savings Customer partially; Fourth, the t-test results obtained t-test 3.106 with a significance level of 0.003. This means that Promotion is able to have a significant influence on the Fleximax Savings Customer Decision partially. Testing the Effect of Product, Price, Place and Promotion on Customer Decisions simultaneously obtained f-statistics results of 3.894 with a significance of 0.007. This result means that all independent variables are able to have a significant influence on customer decisions because the significant value is less than 0.05. The implication of this research is that the management of Bank Panin Dubai Syariah must be able to maintain and be able to improve banking products that are in accordance with the needs of the community, especially Felximax Savings that is able to answer the needs of today's society. With its convenience and advantages. So that many customers are interested in saving their funds with the Fleximax savings product. By paying attention to the marketing mix factors, this can support the running of the company and be able to compete with conventional products that first existed